IS IT NECESSARY TO TEACH THE THEORY OF RELATIVITY IN GENERAL PHYSICS COURSE - Sergey N. Kolgatin (Obrazovanie i Nauka, 2015)
The aim of the present investigation is to discuss and study the general structure of the course of Physics at the high school in an extended sense. In a narrower sense, the author wonders about the necessity for inclusion of the section «Theory of Relativity» in the General Physics course, and discusses the possible site of this issue in the order of presentation.Methods. A method for designing Physics course in modern conditions requires certain sophistication from a lecturer. This is due to the strong reduction of Physics course occurred in recent years, and due to a number of objective and subjective reasons. Planning the course structure, one has to make the selection of most significant questions sacrificing minor and less significant issues. This process is particularly exacerbated by severe restrictions on the time allowed for the subject. It is necessary to re-examine the content of the course due to the recent reduction in lecture hours on Physics. In this case, it would be undesirable to neglect the substantial parts of the subject content which are important conceptually or in its applications, e.g. the Relativity Theory. The author discusses two ways of disposition of the relevant material in the course structure, and correlates them with the required level of Physics teaching. In the first approach the Relativity Theory course is considered as a part of Modern Mechanics and is placed in the first semester immediately following Kinematics. In the second approach, Relativistic Physics is presented as a result of deduction, as a generalized theory explaining the unity of the world and the objective existence of physical laws; in this case, the section is better to locate after Optics, immediately before Atomic Physics.Results. As a result of consideration, the author proves the conclusion that the inclusion of the Relativistic Theory course in a number of sections of General Physics is necessary. The author offers a list of questions for each of the anticipated levels of development of the subject and associates the place and depth of teaching relativism with these levels.Scientific novelty. Based on long-term teaching experience, the author summarizes and presents own research findings and results. The results of the investigation are presented in its original form, suitable for use as charts and tables.Practical significance. The author hopes that his results will be useful for a wide range of Physics teachers, mostly for the leading lecturers and trainers admitted to planning lectures and to the development of concepts in Physics teaching in higher education.